The Political Economy of Kazakhstan: A Case of Good Economics, Bad Politics? - Simon Commander; Ruta Prieskienyte (Institute of Labor Economics (IZA), 2021)
Can autocracies and their associated institutions successfully implement economic policies that promote growth and investment? Can 'good economics' somehow offset the effects of 'bad' politics? Kazakhstan is a case where an autocratic regime has actively projected market-friendly policies and attracted significant amounts of incoming investment. These policies are to some extent reflected in the country's governance ratings, although there has been a significant amount of investment disputes that question the attachment to the rule of law. Moreover, the political regime remains strongly personalized around the founder President, his family and associates. This is reflected in the economics of the autocracy whereby a large public sector and a set of privately held businesses coexist to mutual benefit. The latter have been formed around a very small number of highly connected individuals whose initial accumulation of assets allows them also to act as necessary gatekeepers for entrants. Competition as a result remains limited in both economic and political domains. Yet, uncertainties over the future leadership, along with latent rivalry over access to resources and markets, make the political equilibrium quite fragile. In short, 'bad' politics both squeezes the space for, and distorts the benefits from, 'good' economics.
Keywords: D72; H11; L14; P26; 330; political networks; autocracy; investment